Characteristic Profiles of Activities of Daily Living and Relationship with Cognitive Performance in Thai Elderly with Different Stages from Normal Cognitive Function, Mild Cognitive Impairment to Dementia. Issue 4 (7th August 2016) - Charernboon, Thammanard; Lerthattasilp, Tiraya
ABSTRACT: Objective: The objectives were twofold—first, to evaluate the functional difference among normal cognitive elderly, mild cognitive impairment (MCI), and people with dementia; and second, to investigate the relationship between cognitive performance and functional abilities.Method: The Disability Assessment for Dementia (DAD) was administered to 90 participants: 20 normal controls (NC), 20 with MCI, 25 with mild dementia, 15 with moderate dementia and 10 with severe dementia patients.Results: The mean (SD) scores on instrumental activities of daily living (IADL) were 94.8 (6.4) for NC, 89.1 (9.9) for MCI, 33.6 (21.7) for mild dementia, 13 (12.2) for moderate dementia and 1.7 (4.2) for severe dementia. MCI participants presented slightly noticeable deficit in one IADL domain: 'finance and correspondence', whereas mild dementia presented deficit in all six IADL domains. Scores of basic activities of daily living (BADL) of the NC and MCI groups were equal at a perfect 100. The scores were slightly reduced in mild dementia patients (92.7 [12.3]) and were decreased in moderate (68.6 [26.4]) and severe dementia participants (10 [14.4]).Conclusions: Our studies demonstrated that IADL can be subtly impaired in people with MCI, but markedly impaired in those with mild dementia. BADL begin to decline in moderate dementia and then reach a level of severe impairment in severe dementia.